The Effect of Income, Financial Knowledge, and Personality on Financial Management Practices - Rismala Dwiyanti; Abdul Rahman Laba; Andi Ratna Sari Dewi (Magister Management, Hasanuddin University, 2021)
Financial management practices applied by SMEs have been concerned by many researchers. This study aims to determine the effect of income, financial knowledge, and personality on financial management practices in SMEs in Makassar City. The samples used are SMEs that have been registered in the Cooperatives Office of South Sulawesi Province. The sampling technique used was the purposive sampling technique. This research data comes from a questionnaire made with a Likert scale and analysis using multiple linear regression. The results of the study found that income, financial knowledge, and personality can be associated with financial management practices with a positive and significant sign. It explains that the income earned by driving up financial capability and is also the same for financial knowledge and personality behavior.